2010
DOI: 10.1002/pen.21740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microfiber reinforcement on the morphology, electrical, and mechanical properties of the polyethylene/poly(ethylene terephthalate)/carbon nanotube composites

Abstract: In situ microfiber reinforced conductive polymer composites consisting of high-density polyethylene (HDPE), poly(ethylene terephthalate) (PET), and multiwalled carbon nanotube (CNT) were prepared in a twin screw extruder followed by hot stretching of PET/CNT phase in HDPE matrix. For comparison purposes, the HDPE/PET blends and HDPE/PET/CNT composites were also produced without hot stretching. Extrusion process parameters, hot-stretching speed, and CNT amount in the composites were kept constant during the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
(73 reference statements)
1
21
0
Order By: Relevance
“…Cardinaud and McNally [2] theoretically predicted and experimentally proved the preferential localization of MWCNTs in the PET phase of several PET/LDPE blends. The same result was achieved by Yesil et al [3] for PET/HDPE and Goldel et al [4] found that even minor differences in the wetting behavior were enough for MWCNTs with large aspect ratios to migrate to the more favorable PC phase in PC/SAN blends. Moreover, the wetting coefficient also proved to be successful at predicting the locations of three different silica nanoparticles in LDPE/PEO blends [5].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Cardinaud and McNally [2] theoretically predicted and experimentally proved the preferential localization of MWCNTs in the PET phase of several PET/LDPE blends. The same result was achieved by Yesil et al [3] for PET/HDPE and Goldel et al [4] found that even minor differences in the wetting behavior were enough for MWCNTs with large aspect ratios to migrate to the more favorable PC phase in PC/SAN blends. Moreover, the wetting coefficient also proved to be successful at predicting the locations of three different silica nanoparticles in LDPE/PEO blends [5].…”
Section: Introductionsupporting
confidence: 73%
“…The polymers used in this study were: a) poly(methyl methacrylate) (PMMA) Plexiglas 6N, from Evonik Industries (an amorphous thermoplastic moulding compound, with T g =99ºC, MVR at 230 ºC/3.8 kg = 12 cm 3 /10min, and melt density= 1.10 g/cm 3 ); b) low density polyethylene (LDPE) LD605BA, from ExxonMobil (a general purpose LDPE grade, with T m =108 ºC, MFI at 190 ºC/2.16 kg = 6.5 g/10min, and melt density= 0.76 g/cm 3 ). Non-functionalized multi-walled carbon nanotubes (MWCNTs) NC7000, from Nanocyl S.A, Belgium were used.…”
Section: Methodsmentioning
confidence: 99%
“…This is typical behaviour for fibre reinforced composites [15]. The decrease of SB with rPET concentration in uncompatibilized blends were due to the low strain at break and brittle nature of PET fibres, which restrict the mobility of polymer molecules [13] [16]. This is an indicator of the material flexibility, which shows that the incorporation of rPET makes the rHDPE-rich blend stronger but more brittle.…”
Section: Blends Preparation and Characterizationmentioning
confidence: 83%
“…The compatibilized blends containing 45 wt% and 50 wt% rPET fibres could not be compression molded for tensile testing. The presence of a compatibilizer in the blend hinders the nucleation effect of rPET fibres, leading to a little thermal contraction; however, rHDPE undergoes crystallization and contracts strongly during cooling from the melt [16]. Meanwhile, the introduction of relatively low stiffness compatibilizer may firstly produce plastic deformation at the interface [17].…”
Section: Figure 2 Andmentioning
confidence: 99%
“…They found that after an initial increase in tensile strength, the addition of microfibers and MWCNTs decreased the performance since there was a lack of compatibility with the polymer phase beyond 30 wt% loading of PET [29].…”
Section: Mechanical Propertiesmentioning
confidence: 99%